Academic Fraud Mahasiswa pada Sistem Pembelajaran Daring dengan Self-Efficacy sebagai Variabel Moderasi: - Nabila Putri Alivia; Saiful Anwar (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to analyze: Student Academic Fraud in Online Learning Systems with Self-Efficacy as Moderating Variable: Dimensions of Diamond Theory and Information Technology Abuse. The population used in this study were undergraduate students majoring in accounting at UPN Veterans East Java, Class of 2018 totaling 224 students and Class of 2019 totaling 293 students, so the total population in this study was 517 Accounting students at UPN Veterans East Java, Class of 2018 and 2019. Research This study uses a probability sampling technique and the results obtained are 226 respondents. The analysis in this study uses the Partial Least Square (PLS) approach. The results of this study show that pressure and opportunity has a positive but not significant or no effect on accounting student academic fraud in the online learning system. Rationalization, ability, and misuse of information technology has a positive effect on accounting student academic fraud in online learning systems. Self-efficacy is able to moderate, more precisely, strengthen the influence of pressure on accounting student academic fraud in the online learning system. Self-efficacy is not able to moderate the effect of opportunity, rationalization, ability, and misuse of information technology on accounting student academic fraud in the learning system. Keywords: Pressure, Opportunity, Rationalization, Ability, IT Abuse, Self Efficacy, Academic Fraud